The influence of particle chain-magnetic field spatial location, frequency, dynamic strain amplitude and the prestrain on the mechanical performance of anisotropic magneto-rheological elastomer - Bochao Wang (Elsevier, 2021)
Although there are literatures to characterize the properties of anisotropic magneto-rheological elastomer (MRE), more attention is paid when the particle chain is parallel to the applied magnetic field. However, in prospective of modeling and application design, mechanical characterization of anisotropic MRE under other particle chain-magnetic field spatial locations is needed. Herein, mechanical properties of anisotropic MRE with four kinds of particle chain-magnetic field spatial locations under varies frequencies, strain amplitudes and prestrains are tested. It shows that even the particle chain is perpendicular to the magnetic field, there exists an obvious MR effect. Besides the attraction of adjacent magnetized particles, the Maxwell stress tensor also contribute to the MR effect. Furthermore, an obvious strain amplitude dependent viscoelastic behavior is exhibited for anisotropic MRE. Moreover, the MR effect and the loss factor decrease as the increase of prestrain. The investigation contributes to the designing, modeling and applications of anisotropic MRE.